Of palm wine, women, and war the Mongolian naval expedition to Java in the 13th century - Bade, David W. (Institute of Southeast Asian Studies, 2013)
What would a history that put women at the centre of the rise and fall of kingdoms be like? When the armies of Khubilai arrived on Java in 1293, they found themselves in the middle of two warring states. Two historical traditions developed concerning the ensuing events: the official Chinese dynastic records in which no women are mentioned, and a number of Javanese histories and poems in which everything depends upon the actions and fates of certain women. The Chinese account has long been regarded as factual, whilst the Javanese versions have been dismissed as mere romance, their women stereotypical representations of male fantasies. But what happens if the women and the narratives about them are taken seriously rather than dismissed? Of Palm Wine, Women and War offers just such a reading.